Portrait of a Contender: Patrizia Anesa - Anesa, Patrizia (Language at Work - Bridging Theory and Practice, 2010)
This summer, Patrizia Anesa kindly took the time to speak with “Language at Work –Bridging Theory and Practice” about her professional experience at the University of Bergamo, Italy. Teaching at the Faculty of Economics and the Faculty of Education, Patrizia is also affiliated with CERLIS (Research Centre for the study of Specialized Languages).